2022
DOI: 10.3390/ijerph19031044
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward: Understanding Correlates of Physical Activity and Sedentary Behaviour during COVID-19 in Children and Adolescents—An Integrative Review and Socioecological Approach

Abstract: Novel coronavirus disease 2019 (COVID-19) pandemic restrictions have negatively impacted physical activity (PA) and sedentary time/behaviour. This integrative review systematically explored the socioecological factors that impacted and influenced these movement behaviours in children and adolescents during the pandemic. Five electronic databases were systematically searched in January 2021, with data extracted from 16 articles (n = 18,352; 5–17 years; 12 countries). Risk-of-bias was assessed using the Mixed Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…In the last few years, different authors [ 53 , 54 , 55 , 56 , 57 ] have adopted this approach to assess physical inactivity. In a cross-sectional way, they indicate that at the intrapersonal level, gender, age, ethnic group, and self-concept are relevant aspects, while at the interpersonal level, the family environment and meeting with friends are key points to explain engagement in physical activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, different authors [ 53 , 54 , 55 , 56 , 57 ] have adopted this approach to assess physical inactivity. In a cross-sectional way, they indicate that at the intrapersonal level, gender, age, ethnic group, and self-concept are relevant aspects, while at the interpersonal level, the family environment and meeting with friends are key points to explain engagement in physical activities.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a risk factor for worsening sleep quality, increased stress, and the development of depression and anxiety symptoms (24)(25)(26). Second, it is reflected in the reduction of physical activity among young people as a result of the lockdown, which has now been confirmed by numerous studies (27)(28)(29). More exercise can be effective in protecting one's mental health, such as preventing the emergence and development of anxiety and depression (30,31), but the current situation of young people today is deviating from this.…”
Section: E Ect Mechanisms Within Each Cluster Effect Mechanism In Clu...mentioning
confidence: 97%
“…Thus, perceived behavioral control or self-efficacy could be salient mediators for the relationship between structural barriers toward using exercise spaces and intentions and behavior with respect to being physically active. Research has indicated that socio-structural factors, such as income [ 25 ] and perceived access to facilities and local opportunities for physical activity [ 26 ], and socio-environmental factors, such as perceived peer support [ 27 ], predict intentions and behavior mediated by social cognition constructs such as attitudes [ 28 ].…”
Section: An Integrated Approach To Physical Activity Determinantsmentioning
confidence: 99%